Β-Lactoglobulin–fucoidan nanocomplexes: Energetics of formation, stability, and oligomeric structure of the bound protein. (August 2022) - Burova, Tatiana V.; Grinberg, Natalia V.; Dubovik, Alexander S.; Plashchina, Irina G.; Usov, Anatolii I.; Grinberg, Valerij Y.
Abstract: Interaction of β-lactoglobulin (BLG) with a sulfated polysaccharide isolated from the brown alga Fucus vesiculosus (fucoidan, FVF), was studied by nephelometry, high-sensitivity differential scanning calorimetry, and sedimentation velocity as a function of pH and the polysaccharide/protein ratio. FVF–BLG complexes were found over the pH 2.5–6.0 range. The complexation was accompanied by the decrease in the conformational stability of BLG at pH < pI 5.2 of the protein where FVF and BLG were oppositely charged. Near pI of the protein and at the pH values larger a bit than pI, where BLG has a large dipole moment or carries a small negative charge, the complexation appeared as changes in the oligomeric state of the protein. Binding curves of BLG to FVF were obtained at pH 3.0 and 6.0 according to the DSC and sedimentation velocity data. Binding constants were evaluated: 3.6 × 10 3  M −1  at pH 3.0 and 2 × 10 4  M −1  at pH 6.0. Correlations between the denaturation enthalpy and temperature for the free and bound protein in terms of Kirchhoff's law indicated that the denaturation of both forms of the protein is associated with comparable changes in the accessible surface area of the BLG molecule. It means that the binding of BLG to FVF does not perturb the hydrophobic core of the protein. Graphical abstract: Image 1 Highlights: Depending on pH, FVF and BLG form of interpolyelectrolyte, charge-dipole, or non-electrostatic complexes. Interpolyelectrolyte complexation reduces BLG conformational stability. Charge-dipole or non-electrostatic complexation increases slightly BLG conformational stability. In all complexes, BLG is mainly in a dimeric state.